Transradial Approach for Neuroendovascular Procedures: A Single-Center Review of Safety and Feasibility - Goldman, D.T.; Bageac, D.; Mills, A.; Yim, B.; Yaeger, K.; Majidi, S.; Kellner, C.P.; De Leacy, R.A. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: In recent years, the transradial approach has become more widely adopted for neuroendovascular procedures. The purpose of this study was to evaluate the safety and feasibility of a transradial approach and distal transradial access for neuroendovascular procedures in a single center.MATERIALS AND METHODS: Retrospective analysis was performed for all patients who underwent transradial approach or distal transradial access neuroendovascular procedures from January 2016 to August 2019 at a single center. Exclusion criteria included a Barbeau D waveform, a radial artery of <2 mm on sonographic evaluation, and known radial artery occlusion. Procedures were evaluated for technical success (defined as successful radial artery access and completion of the intended procedure without crossover to an auxiliary access site), complications, and adverse events during follow-up at 30 days.RESULTS: The transradial approach or distal transradial access was attempted in 279 consecutive patients (58.1% women; median age, 57.7 years) who underwent 328 standard or distal transradial approach procedures. Two-hundred seventy-nine transradial approach and 49 distal transradial approach procedures were performed (cerebral angiography [n = 213], intracranial intervention [n = 64], head and neck intervention [n = 30], and stroke intervention [n = 21]). Technical success was 92.1%. Immediate adverse events (2.1%) included radial access site hematoma (n = 5), radial artery occlusion (n = 1), and acute severe radial artery spasm (n = 1). Thirty-day adverse events (0.3%) included a radial artery pseudoaneurysm (n = 1). Twenty-six cases (7.9%) required crossover to transfemoral access.CONCLUSIONS: The transradial approach for neuroendovascular procedures is safe and feasible across a wide range of neuroendovascular interventions.dTRAdistal transradial approachTFAtransfemoral approachTRAtransradial approach